Special aspects of decapod crustaceans growth in recirculating aquaculture systems as exemplified by Australian crayfish Cherax quadricarinatus (Decapoda: Parastacidae) - Borisov, R. R.; Nikonova, I. N. (Marine Biological Journal, 2018)
The volume of decapod crustacean production in aquaculture has steadily increased in recent years. At the same time, studies focused on the intensification of technological processes have gained special popularity. One of such area of focus is the use of recirculating aquaculture system. In this work an analysis of the main factors inhibiting the process of intensification of the cultivation of decapod crustaceans in the recirculating aquaculture system was carried out as exemplified by Australian crayfish Cherax quadricarinatus. The main factors are cannibalism and the suppression of small crayfishes by large individuals. In the experiments, the influence of group and individual housing, length frequency and tank size on growth and survival rate was studied. All individuals used in the experiment were obtained from one female. The duration of the experiments was six months. A positive correlation of cannibalism with the stocking density was revealed. The formation of one-two dominant individuals suppressing the growth of the remaining individuals of the group was observed in small-sized tanks. In individual housing the grows rate of small crayfishes was higher than that of large ones. Experiments with different-sized juveniles showed that the size separation allows to obtain faster and more evenly growing groups, but it does not solve the problem of cannibalism. Considering the results, it is recommended to provide size classification two times in the first three months and decrease the stocking density. Cannibalism can be excluded only with the individual housing.